Mengambil Nilai Persatuan dan Kesatuan dari Belajar Biografi KH. Muhammad Syuhud - Isno, Mohammad (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2019)
The opening of the country's skates due to the emergence of social media is also a challenge in itself. With the widespread use of social media, human relations between countries have become increasingly distant. With the relationship between people in various countries, it is possible to influence each other to influence between various interests. It could be that various interests could endanger a country. It is more so if it brings an ideology that is contrary to the state ideology. Because of the enormous challenges in maintaining the unity and integrity of the nation, efforts are needed to maintain as well as cultivate the spirit of national unity and integrity. One of them is by exploring the history of previous figures in their struggle to foster national unity and integrity. One of the struggle figures featured in this paper is KH. Muhammad Suhud.